Floristic diversity of lomas of Lachay (Lima) during "El Niño 1997•98" event - Cano, Asunción Cano (1999)
A total of 146 species of vascular plants, grouped in 124 genera and 52 families were recorded, among August 1997 and December 1998. The Magnolliopsidae (Dicotyledoneae) was the, dominant group with 115 species, 26 genera, and 8 families. There are not records for Gymnosperm. Three species represented the Pteridophyta. The more representative families were, the Asteraceae with 19 species, Poaceae with 16 species and Solanaceae with 13 species.